Analisis Prospektif dalam Keberlanjutan Program Bank Sampah (Studi Kasus di Kelurahan Legian, Kabupaten Badung) - Mianda, Erlika; I Made Endra Kartika Yudha (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The waste bank program is one of the strategies in overcoming waste problems in Legian Village, Badung Regency. This study's goal is to examine the elements that influence the sustainability of the waste bank program and to map the roles and relationships between stakeholders in the waste management system through waste banks in Legian Village, Badung Regency. The study’s approach is a quantitative within descriptive correlational technique and analysis using MACTOR (Matrix of Alliances and Conflicts: Tactics, Objectives and Recommendations) and MICMAC (Cross Impact Matrix Multiplication Applied to Classification). Data were collected through observation, Focus Group Discussion (FGD), and interviews involving nine stakeholders. The results of the analysis show that the role of regulation is very strong in influencing all variables in the system, so it must be the focus of development by policy makers. The actors who play the most important role in supporting the sustainability of the program are the Village and the Legian Aksi Nyata Kaja Waste Bank. A strong alliance of these actors is needed to support the success and sustainability of the program. The implications of this study indicate that strengthening regulations, increasing the capacity of managers, empowering communities, and multi-party collaboration are important steps in supporting the sustainability of the waste bank program.